Discovery of 1, 8-disubstituted-[1, 2, 3]triazolo[4, 5-c]quinoline derivatives as a new class of Hippo signaling pathway inhibitors. Issue 18 (15th September 2019) - Qiao, Jingxin; Lin, Guifeng; Xia, Anjie; Xiang, Zhiyu; Chen, Pei; Zhang, Guo; Li, Linli; Yang, Shengyong
Graphical abstract: Abstract: Inhibitors of the Hippo signaling pathway have been demonstrated to have a potential clinical application in cases such as tissue repair and organ regeneration. However, there is a lack of potent Hippo pathway inhibitors at present. Herein we report the discovery of a series of 1, 8-disubstituted-[1, 2, 3]triazolo[4, 5- c ]quinoline derivatives as a new class of Hippo pathway inhibitors by utilizing a cell line-based screening model (A549-CTGF). Structure-activity relationship (SAR) of these compounds was also discussed. The most potent compound in the A549-CTGF cell assay, 11g, was then evaluated by real-time PCR and immunofluorescence assays. Overall, this study provides a starting point for later drug discovery targeting the Hippo signaling pathway.